The Jesuit Order as a Synagogue of Jews Jesuits of Jewish Ancestry and Purity-of-Blood Laws in the Early Society of Jesus - Maryks, Robert Aleksander (Studies in Medieval and Reformation Traditions, 2009)
In The Jesuit Order as a Synagogue of Jews the author explains how Christians with Jewish ancestry went within less than forty years from having a leading role in the foundation and development of the Society of Jesus to being prohibited from membership in it. Readership: All those interested in converso and Jesuit history, the history of Catholicism, the history of late medieval and early modern Iberia and Italy, as well as Spanish literature historians, historians of law, and theologians.